Géographie du Paludisme dans la région de Libreville-Owendo-Akanda, Gabon - Mbouloungou, Alexis; Koumba, Aubin Armel; Mombo, Jean Bernard; Iyangui, Nadine Ndonghan; Mavoungou, Jacques François; Djeki, Jules (European Scientific Journal, ESJ, 2019)
In order to determine the geography of malaria, to know the spatial distribution of health facilities and to identify malaria risk areas in LibrevilleOwendo-Akanda area, a study was conducted from july 2016 to june 2017. This study consisted of collecting hospital morbidity data and characterizing public and private health structures in the study area. The malaria data were collected in the clinics using the pre-designed and tested collection forms. Moreover, the cartography of the health structures and chiefdoms of the different neighborhoods from which each patient came was made using a GPSMAP 62s (Garmin). The spatial analyzes were done in ArcGIS 10.3 software according to the Hot Spot model, to identify areas at risk of malaria. Thus, 211 private and public health structures divided into 12 types were identified. These structures are unequally distributed in the LibrevilleOwendo-Akanda region. The best represented are the private medical surgeries (n = 62 ; 29.38%), the drugstores (n = 39 ; 18.48%), the structure for nursing treatment (n = 36 ; 17.06%). On the other hand, the least represented are the medical centers (n = 2 ; 0.95%) and childbirth clinics (n = 1 ; 0.47%). Finally, the spatial analyzes made it possible to show that the clinical malaria prevalence is higher (hot spots) in the districts of the commune of Libreville than in the neighborhoods of the two other neighboring communes that are Owendo and Akanda. The results obtained contribute to make known the spatial distribution of health facilities and hot spots of malaria in the area of Libreville-Owendo-Akanda. Afin de déterminer la géographie du paludisme, de connaître la distribution spatiale des formations sanitaires et d’identifier les zones à risque palustre dans la region de Libreville-Owendo-Akanda, une étude a été menée de juillet 2016 à juin 2017. Cette étude a consisté à récolter les données de morbidité palustre hospitalière et à caractériser les structures sanitaires publiques et privées de ladite zone. Les données de paludisme ont été collectées dans les cliniques au moyen des fiches de collecte pré-conçues et testées. De plus, la cartographie des structures de santé et des chefferies des différents quartiers, d’où provenait chaque malade, s’est faite à l’aide d’un GPS-MAP 62s de marque Garmin. Des analyses spatiales ont été faites dans ArcGIS 10.3 selon le modèle des Hot Spots, pour identifier les zones à risques du paludisme. Ainsi, 211 structures privées et publiques de santé reparties en 12 types ont été répertoriées. Ces structures sont inégalement réparties dans la région de Libreville-Owendo-Akanda. Les mieux représentés sont les cabinets médicaux privés (n=62 ; 29,38%), les pharmacies (n=39 ; 18,48%), les cabinets des soins infirmiers (n=36 ; 17,06%). Tandis que les moins représentés sont les centres médicaux (n=2 ; 0,95%) et les cabinets d’accouchement (n=1 ; 0,47%). Enfin, les analyses spatiales faites ont permis de montrer que la prévalence palustre clinique est plus élevée (hot spots) dans les quartiers de la commune de Libreville que dans les quartiers des deux autres communes voisines que sont Owendo et Akanda. Les résultats obtenus concourent à faire connaitre la distribution spatiale des formations sanitaires et des hot spots du paludisme dans la région de Libreville-Owendo-Akanda.